Cell‐free and concentrated ascites reinfusion therapy versus large‐volume paracentesis for the treatment of cirrhotic patients with refractory ascites: A multicenter prospective observational study. Issue 3 (3rd December 2022) - Hanai, Tatsunori; Kawaratani, Hideto; Nagano, Junji; Suii, Hirokazu; Sakamaki, Akira; Arase, Yoshitaka; Nakanishi, Hiroyuki; Kogiso, Tomomi; Okubo, Tomomi; Miwa, Takao; Shimizu, Shogo; Hige, Shuhei; et al.
Abstract: Aim: Cell‐free and concentrated ascites reinfusion therapy (CART) and large‐volume paracentesis (LVP) with albumin infusion are useful for managing refractory ascites (RA). However, it remains unclear which therapy is more effective in patients with cirrhosis with RA. Methods: From June 2018 to March 2022, 25 patients with RA treated with CART or LVP with albumin infusion were enrolled in this multicenter prospective observational study to investigate the number of abdominal paracenteses, albumin preparations used, and drainage volume during an 8‐week observation period. Results: Among all patients at entry (median age, 63 years; 52% men; 60% Child–Pugh B and 40% Child–Pugh C), 92% were treated with furosemide (median, 20 mg/day), 92% with spironolactone (25 mg/day), and all with tolvaptan (7.5 mg/day). Patients with RA had a poor health‐related quality of life (HRQOL) and prominent ascites‐related symptoms. Four of the 20 eligible patients were treated with CART, 11 with LVP with albumin infusion, and five with their combination. The median number of paracenteses, total drainage volume, and albumin infusions were 1.5, 7.4 L, and 0, respectively, in the CART group; 5.0, 22.0 L, and 5.0, respectively, in the LVP group; and 5.0, 30.0 L, and 5.0, respectively in their combination group. The treatment effects did not differ significantly among the three groups regarding weight loss, liver function, renal function, electrolytes, and HRQOL. However, patients treated with CART had fewer paracenteses and albumin infusions than those treated with LVP. Conclusions: CART and LVP have comparable therapeutic efficacy for RA in patients with cirrhosis.